Correlating sleep habit to blood pressure in the apparently healthy Nepalese adults - Amatya Nepal, Mrigendra (International Journal of Pharmaceutical & Biological Archive, 2015)
Correlating sleep habit to blood pressure in the apparently healthy Nepalese adults